SIOP components: Application and assessment through PBL in a content-language college classroom - Luisa Cecilia Chavez (Universidad de La Sabana, 2013)
This article describes the circumstances and outcomes of an on-going research which explores the effectiveness of explicitly exercising a relationship between two of the eight components from the constructivist model SIOP (Sheltered Instruction Observation Protocol): Application and Assessment, through PBL (Project-Based Learning) in a content-language context at university level. It begins by compiling thoughts from various theorists who emphasize the importance of opening real application avenues to assess students learning. The research took place in a bilingual college in Bogotá, Colombia, during the second semester of 2011 and the first semester of 2012.  The data analysis was taken from a group enrolled in a sixth semester class.  Results make clear that through accompanying students through the proper use of PBL ladder, as an application tool, they will be able to value their own process of learning.